CAN INVESTMENT PROFESSIONALS CONSISTENTLY BEAT THE MARKET? AN INVESTIGATION OF UNIT TRUST/OEIC PERFORMANCE AND THE ÃÂÃÂ¢ÃÂÃÂÃÂÃÂHOT HANDÃÂÃÂ¢ÃÂÃÂÃÂÃÂ PHENOMENON IN THE UK, 2004 - 2008 - Kurniadi, Agus (2008)
This study analyzes the performance of 2003ÃÂÃÂ¢ÃÂÃÂÃÂÃÂs Top 40 UK unit trusts over the period from January 2004 through June 2008. Our main research objectives are twofold. First, we wish to determine whether investment professionals such as unit trust managers possess superior stock-picking skills which enable them to outperform the market return. Second, if they manage to do just that, can their performance persist over the short-to-medium term? We apply traditional performance measures that are based on the single-factor capital asset pricing model (CAPM) such as Sharpe ratio, Treynor ratio and Jensen alpha. We find evidence that unit trust managers on average as a group are unable to neither beat the market nor maintain their performance level consistently over our research period.